Keislaman Negeri Muslim (Kontestasi dan Konsep Negara Agama Perspektof Gus Sholah dan Gus Dur) - Khayati, Siti Qomala (Proceedings of Annual Conference for Muslim Scholars, 2019)
This article will discuss discursive concept of Islamic State and its implication to the built norm of Muslim society; either inside or integrated nation which Islam became a major religion, such as Indonesia, Malaysia, and so on. This article also will explore the conceptions of two Nahdlatul Ulama’ scholars, the son of Religious Manister in Older Era, namely: A. Wahid Hasyim. Methodologically, this article is qualitative research based on library and phenomenological approach. In the conclusion, this article found that, rarely, Islamic stance will make Muslim become un-progressive caused their beliefs contestation inside, no solidarity action of Moslem to make mutual understanding, and in the end as critical substances of this research was Islam as ideology just appears in campaign of politics in public sphere; neither an actual beliefs to build the nation without comparing the system. Therefore, the Islamic stance on Islamic Nation, actually, must be substantive values for building the nation, not only an ideology to contest itself or political identity as a Muslim.